2019
DOI: 10.1007/s11420-018-9646-0
|View full text |Cite
|
Sign up to set email alerts
|

How Should We Define Clinically Significant Outcome Improvement on the iHOT-12?

Abstract: Background: There is increased emphasis on efficiently administering patient-reported outcome measures (PROMs). The International Hip Outcome Tool-12 (iHOT-12) is a short-form version of the iHOT-33, and relatively little is known about clinically significant outcomes using the iHOT-12. Questions/Purposes: The purpose of this study was to define minimal clinically important difference (MCID) and patient acceptable symptomatic state (PASS) for the iHOT-12 and to identify predictors for achieving these psychomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
94
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 22 publications
3
94
1
Order By: Relevance
“…We used distributional methodology to calculate the MCID for the iHOT-12 and found this to be 13 points. This is very similar to the estimates of other studies that have reported the MCID for the iHOT-12 score [21,22] and although this was not the primary analysis of our study it lends credibility to the representativeness of our underlying dataset.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We used distributional methodology to calculate the MCID for the iHOT-12 and found this to be 13 points. This is very similar to the estimates of other studies that have reported the MCID for the iHOT-12 score [21,22] and although this was not the primary analysis of our study it lends credibility to the representativeness of our underlying dataset.…”
Section: Discussionsupporting
confidence: 89%
“…A further study has also calculated the PASS threshold for the iHOT-12 and found it to be 63 [21]. However, in their study the authors used the external anchor question "Taking into account all the activities you have during your daily life, your level of pain, and also your functional impairment, do you consider that your current state is satisfactory?"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 2year PASS value was then identified by using an receiver operating characteristic (ROC) curve analysis as previously done in prior studies (analysis provided in Appendix 1). 3,23,24,[27][28][29] A sensitivity and specificity of 0.80 was used as the cut-off for determining an acceptable HOS-SS PASS score. Patients were classified as achieving PASS if PASS was achieved on any of the included outcome measures.…”
Section: High Versus Low Function After Hip Arthroscopymentioning
confidence: 99%
“…In this regard, it should be noted that a similar study used an anchorbased method to calculate PASS and reported a threshold score of 63.0 (compared with 75.2 in the study under commentary). 11 Overall, Kivlan et al 9 have provided another data point in the evolving literature on clinically significant outcome. As the authors note, their study findings may help shape how patient outcome on the iHOT-12 is interpreted going forward.…”
mentioning
confidence: 99%